HOLOGRAPHY FOR ROTATING BLACK HOLES - Haryanto M. Siahaan (INTEGRAL, 2013)
Holographic principle and its realization in string theory through AdS/CFT correspondence has given us a new way to study the theory of quantum gravity. Shortly, holography in this context is understood as a duality between a gravitational theory in D+1 dimensions with a eld theory with no gravity living on the boundary with D dimensions. More precisely, the statement of AdS/CFT correspondence is the duality between a gravitational theory in D + 1 dimensional anti-de Sitter (AdS) space and a conformal eld theory (CFT) on the boundary of AdS with D dimensions. In the same spirit of holography, Kerr/CFT correspondence states that the physics of rotating black holes is dual to a two dimensional conformal eld theory on a hypersurface near the black hole's horizon. In this paper, I review the Kerr/CFT correspondence. In this regard, some basic materials about black holes and conformal eld theory that are needed to understand Kerr/CFT correspondence are presented.Keywords: konformal symmetry, black holesPrinsip hologra dan realisasinya dalam teori string melalui korespondensi AdS/CFT telah memberikan cara pandang baru dalam mempelajari teori kuantum gravitasi. Secara ringkas, hologra dalam konteks ini diartikan sebagai dualitas antara teori gravitasi di ruangwaktu berdimensi D + 1 dengan teori medan tanpa gravitasi di daerah batas dari ruangwaktu ini dengan dimensi D. Secara lebih tepat, pernyataan korespondensi AdS/CFT yaitu dualitas antara teori gravitasi di ruang anti-de Sitter(AdS) berdimensi D+1 dengan teori medan conformal (CFT) di ruang batas AdS ini yang berdimensi D. Seiring dengan semangat hologra, korespondensi Kerr/CFT menyatakan bahwa sika lubang hitam berotasi bersifat dual kepada teori medan konformal dua dimensi yang berada pada sebuah irisan ruangwaktu dekat dengan horison lubang hitam terkait. Dalam makalah ini, saya mengulas kembali korespondensi Kerr/CFT. Terkait dengan hal ini, disajikan beberapa materi dasar tentanglubang hitam dan teori medan konformal yang diperlukan dalam memahami korespondensi Kerr/CFT.Kata Kunci: hologra, simetri konformal, lubang hitam.